Pemodelan Nilai Koefisien Manning Terhadap Karakteristik Hidraulika Dalam Simulasi Banjir Menggunakan HEC-RAS Pada DAS Landak, Kalimantan Barat - Laily Fadhilah Sabilal Haque; Irene Yovita Br. Banurea; Arina Mana Sikana; Rian Mantasa Salve Prastica (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
Floods are a serious problem for many countries in the world, including the Landak Regency, West Kalimantan, Indonesia. The floods in the area is a disaster situation for the local community. This study aims to determine the magnitude of the design flood discharge in the study area and to offer alternative scenarios solution for solving floods problem. The research method is in the form of numerical analysis with formulas as well as application assistance to describe the visualization of the situation, starting from watershed analysis, hydrological and hydraulic calculations, and numerical modeling for visualization of water level using HEC-RAS software. Based on the secondary data, the analysis of rainfall for the 50 years return period in a Nakayasu flood discharge is 13884.02 m³/second. This value are then used for simulation in the HEC-RAS application. The scenario used during the simulation is the steady flow. The simulation results are useful for describing the choice of problem solutions that will be determined at the end of the research.